1999
DOI: 10.1002/(sici)1096-8628(19991015)88:5<458::aid-ajmg3>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Association of a functional ?-opioid receptor allele (+118A) with alcohol dependency

Abstract: Genetic association studies have implicated the TaqI A1 allele of the human dopamine D2 receptor gene (DRD2) as a risk-determining factor for alcohol dependency. However, as alcoholism is a disease of polygenic inheritance, the percentage of overall disease variance explained by the TaqI A1 allele is small. In searching for other genetic loci that may, either alone or in combination with DRD2, enhance prediction of alcoholism, we have found a novel association between a functional coding variant (+118A) within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 19 publications
1
54
0
3
Order By: Relevance
“…A number of studies have reported positive association between OPRM1 functional variant A118G and OD, [27][28][29][30] cocaine dependence (CD) 31 or AD. [31][32][33][34] Moreover, three studies adopting haplotype-based approaches also demonstrated the association between OPRM1 variants and DD or AD. [35][36][37] However, a meta-analysis showed no consistent evidence of an association of the A118G polymorphism with SD.…”
Section: Introductionmentioning
confidence: 93%
“…A number of studies have reported positive association between OPRM1 functional variant A118G and OD, [27][28][29][30] cocaine dependence (CD) 31 or AD. [31][32][33][34] Moreover, three studies adopting haplotype-based approaches also demonstrated the association between OPRM1 variants and DD or AD. [35][36][37] However, a meta-analysis showed no consistent evidence of an association of the A118G polymorphism with SD.…”
Section: Introductionmentioning
confidence: 93%
“…Data from 80 of these cases were reported in our previous study. 7 Detailed information about history of substance use was obtained by means of a structured interview administered by trained graduate-level research assistants. The mean age of the alcoholic sample was 46.9 ± 8.6 years and all but four cases were males.…”
Section: Subjectsmentioning
confidence: 99%
“…Because the endogenous opioid system plays a role in the reinforcing effects of a number of other drugs, we 7 previously investigated a functional coding polymorphism (+118A/G) within the reward-associatedopioid receptor gene (OPRM1) as a risk candidate for alcoholism in samples that were largely Caucasian. Our results supported the AA genotype and A allele as risk factors for alcoholism, with an odds ratio (OR) of 2.10 (Confidence Interval = 1.11-3.98) by genotype.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, two polymorphisms in exon 1 of the gene alter amino acid sequence, A +118 G (Asn40Asp) and C +17 T (Ala6Val), and these have received the most research attention. However, case-control studies have failed to demonstrate a consistent association between OPRM1 sequence variation and the presence of alcohol and/or drug dependence (Bergen et al, 1997;Berrettini et al, 1997;Bond et al, 1998;Kranzler et al, 1998;Sander et al, 1998;Gelernter et al, 1999;Town et al, 1999;Hoehe et al, 2000;Franke et al, 2001;Rommelspacher et al, 2001;Szeto et al, 2001;Schinka et al, 2002;Crowley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%